Forensic veterinary examination of the death of dogs and cats from cases of high temperatures - Harkusha, S.; Bokotko, R.; Kruchynenko, O.; Peredera О. (Scientific Progress & Innovations, 2024)
rensic veterinary examination of damage and death of dogs and cats from high-temperature exposure. It is noted that the negative impact on animal health caused by high-temperature factors is divided into general, which is manifested by heat or sunstroke, and local, in the form of thermal burns, although the latter can cause complications in the form of a general effect known as burn disease. According to the experience of practicing veterinarians, there are numerous cases of burns of dogs and cats of varying severity, as well as heat or sunstroke, which can result in the death of animals. Criminal proceedings in such cases may be initiated in order to identify persons who, through their actions or inaction, may be involved in the disease or death of animals. The most common situations in which animals can be affected by heat and sunstroke are described, namely high air temperature, calm weather, lack or insufficient ventilation, exposure to direct sunlight, lack of shade, water, obesity, and others. The article also describes the breeds of dogs and cats that are most susceptible to this pathology. A list of the most characteristic clinical signs observed in live affected animals, as well as characteristic macroscopic and microscopic changes in heat and sunstroke, the principles of differentiation of these lesions from other diseases and pathological conditions are given. The thermal burns that can occur in dogs and cats, their causes, mechanisms of development of burns and burn disease are characterized in detail. The most common situations in which animals can be affected by heat and sunstroke are described, namely high air temperature, calm weather, lack or insufficient ventilation, exposure to direct sunlight, lack of shade, water, obesity, and others. The article also describes the breeds of dogs and cats that are most susceptible to this pathology. A list of the most characteristic clinical signs observed in live affected animals, as well as characteristic macroscopic and microscopic changes in heat and sunstroke, the principles of differentiation of these lesions from other diseases and pathological conditions are given. The thermal burns that can occur in dogs and cats, their causes, mechanisms of development of burns and burn disease are characterized in detail.